Local Wisdom-Based Transformational Leadership for Psychological Safety and Village Team Performance - Umar Umar; Ibrahim Ibrahim (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
This study develops and tests a local wisdom-based transformational leadership model for enhancing psychological safety and village team performance in Soppeng Regency, Indonesia. The study responds to the need for leadership models that are not only theoretically robust but also culturally grounded in local public-sector settings. A quantitative explanatory design was employed using a structured survey of village government officials. The proposed model positions local wisdom-based transformational leadership as the independent variable, psychological safety as the mediating variable, and village team performance as the outcome variable. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The illustrative results indicate that local wisdom-based transformational leadership has a positive and significant effect on psychological safety and village team performance. Psychological safety also has a positive and significant effect on village team performance and partially mediates the relationship between leadership and performance. These findings suggest that leadership practices grounded in sipakatau, sipakalebbi, sipakainge, lempu, getteng, and ada tongeng can strengthen interpersonal trust, openness, mutual respect, and collaborative performance within village government teams. This study contributes to public-sector leadership and human resource management literature by integrating transformational leadership theory with Bugis local wisdom values in the context of village governance. Practically, the findings highlight the importance of culturally sensitive leadership development programs for village officials